Խորհրդային եւ յետխորհրդային փուլերի արտացոլումները հայոց խաղային մշակոյթում - Ասատրեան, Հռիփսիմէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Начиная с 20-х годов прошлого века, в советском начальном этапе игры, сформированные в армянской реальности, получили социально-политическую окраску. В них начали затрагиваться такие темы, как война и бой, героизировались имена таких личностей, как В. Чапаев и В. Ленин․ At the beginning of the 1920s, at the first phase of the Soviet era, the games outlined in the Armenian reality received a socio-political coloring. In the games, such themes as war and battle began to be touched upon and such individuals as V. Chapaev and V. Lenin started becoming heroes.
Keywords: History; Ethnography